Impaired health-related quality of life after chemoradiotherapy for anal cancer: Late effects in a national cohort of 128 survivors. (May 2013) - Bentzen, Anne Gry; Balteskard, Lise; Wanderås, Eva Hoff; Frykholm, Gunilla; Wilsgaard, Tom; Dahl, Olav; Guren, Marianne Grønlie
Abstract Background. Chemoradiotherapy is an effective treatment for anal cancer, yet from follow-up many survivors seem to suffer from late effects. Data of long-term health-related quality of life (HRQOL) in anal cancer survivors are limited, and there is a growing interest in cancer survivorship. Material and methods. A national cohort of all anal cancer survivors treated with curative chemoradiotherapy in 2000–2007 was invited to a cross-sectional study. Of 199 eligible survivors, 128 (64%) returned the questionnaires, the median time since diagnosis was 66 months. The median age was 61 years and 79% were women. HRQOL was evaluated with EORTC questionnaires QLQ-C30 and QLQ-CR29, and neurotoxicity with the Scale of Chemotherapy-Induced Neurotoxicity. An age- and sex-matched reference group of volunteers (n = 269) not treated for pelvic cancer answered the same questionnaires. Results from QLQ-C30 of the reference group were compared to Norwegian and Dutch normative data. Results. The mean scores of anal cancer survivors were poorer compared to volunteers and normative data. Anal cancer survivors reported significant impairment of function, especially social and role function, compared to the volunteers (difference ≥ 20 points, p < 0.001). Survivors had markedly increased scores for fatigue, dyspnoea, insomnia and diarrhoea (difference ≥ 15 points, p < 0.001). The global quality of life was significantly reduced (difference 15 points, p < 0.001). Anal cancer survivors had increased stool frequency, more buttock pain, flatulence, faecal incontinence, impotence (males), dyspareunia and reduced sexual interest (females) (difference ≥ 15 points, p < 0.001). There was increased frequency of tinnitus in survivors treated with cisplatin-based chemotherapy (p = 0.004). Conclusions. Survivors after chemoradiotherapy for anal cancer have significant long-term impairment of HRQOL. Reduced social, role and sexual function, and increased diarrhoea, incontinence for gas and stools, and buttock pain were commonly reported. Increased awareness of this may lead to better management of late effects and better care for cancer survivors.